ESTIMATION OF CARDIAC SURGERY RESULTS - Charyshkin, Alexey Leonidovich; Yudin, Alexander Nikolaevich (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Estimation of cardiac surgery results after median sternal incision. Methods: This work contains the results of surgical treatment of 220 patients who had cardiac surgeries performed by means of the median sternal incision at the State Healthcare Institution Ulyanovsk Regional Clinical Hospitalâ€ during 2000â€“2014. Results: The following surgical interferences were made: Coronary artery bypass grafting â€“ 14 (6.3%), mammary coronary bypass â€“ 5 (2.3%), combined coronary artery and mammary coronary bypass grafting â€“ 81 (36.8%), aortic valve replacement â€“ 53 (24.1%), mitral valve replacement â€“ 44 (20%), atrial septal defect plasty â€“ 7 (3.2%), ventricular septal defect plasty â€“ 3 (1.4%), myxomas â€“ 5 (2.3%), and mediastinal neoplasms removal â€“ 8 (3.6%). The most frequent early complications after median sternal incision were wound pyoinflammatory complications that were observed in 32 (14.5%) patients, pneumonia â€“ defined in 17 (7.7%) patients, mediastinitis â€“ found in 5 (2.3%) patients, sepsis â€“ detected in 2 (0.9%) patients, and acute cerebrovascular disease â€“ observed in 1 (0.5%) patient. The fatal outcome was observed in 2 (0.9%) cases; the cause of death of the first (0.5%) patient was multiple organ failure against the background of sepsis, and the cause of death of the second patient (0.5%) was acute cerebrovascular disease. Conclusion: The most frequent early post-operative complications the patients have after cardiac surgeries are wound pyoinflammatory complications (14.5%), pneumonia (7.7%), and mediastinitis (2.3%).